Demethyleneberberine alleviated the inflammatory response by targeting MD-2 to inhibit the TLR4 signaling - Zhao, Yaxing; Liu, Peng; Luan, Haofan; Jiang, Hua; Xu, Yingmei; Zhang, Yuanqiang; Zhang, Yubin; Li, Ruiyan (Frontiers in Immunology, 2023)
Introduction The colitis induced by trinitrobenzenesulfonic acid (TNBS) is a chronic and systemic inflammatory disease that leads to intestinal barrier dysfunction and autoimmunedisorders. However, the existing treatments of colitis are associated with poor outcomes, and the current strategies remain deep and long-time remission and the prevention of complications. Recently, demethyleneberberine (DMB) has been reported to be a potential candidate for the treatment of inflammatory response that relied on multiple pharmacological activities, including anti-oxidation and antiinflammation. However, the target and potential mechanism of DMB in inflammatory response have not been fully elucidated. Methods This study employed a TNBS-induced colitis model and acute sepsis mice to screen and identify the potential targets and molecular mechanisms of DMB in vitro and in vivo. The purity and structure of DMB were quantitatively analyzed by high-performance liquid chromatography (HPLC), mass spectrometry (MS), Hydrogen nuclear magnetic resonance spectroscopy (1H-NMR), and infrared spectroscopy (IR), respectively. The rats were induced by a rubber hose inserted approximately 8 cm through their anus to be injected with TNBS. Acute sepsis was induced by injection with LPS via the tail vein for 60 h. These animals with inflammation were orally administrated with DMB, berberine (BBR), or curcumin (Curc), respectively. The eukaryotic and prokaryotic expression system of myeloid differentiation protein-2 (MD-2) and its mutants were used to evaluate the target of DMB in inflammatory response. Resluts DMB had two free phenolic hydroxyl groups, and the purity exceeded 99% in HPLC. DMB alleviated colitis and suppressed the activation of TLR4 signaling in TNBS-induced colitis rats and LPS-induced RAW264.7 cells. DMB significantly blocked TLR4 signaling in both an MyD88-dependent and an MyD88-independent manner by embedding into the hydrophobic pocket of the MD-2 protein with non-covalent bonding to phenylalanine at position 76 in a pi–pi T-shaped interaction. DMB rescued mice from sepsis shock induced by LPS through targeting the TLR4–MD-2 complex. Conclusion Taken together, DMB is a promising inhibitor of the MD-2 protein to suppress the hyperactivated TLR4 signaling in inflammatory response.